Improving Students’ Speaking Skills by Utilizing Orai AI-Powered App - Ali, Nurbaiti; Losi, Rizky Vita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Artificial intelligence (AI) presents fresh and innovative learning options for students and learners in the field of English instruction. Artificial intelligence helps improve English language instruction by promoting dialogue and providing students with pertinent feedback. AI in education improves classroom management and boosts teacher efficiency. One kind of AI is Orai, a program that makes the claim that it may be used to enhance public speaking skills. This research aimed to show the improvement of students’ speaking skills by utilizing Orai application. The Classroom Action Research was used as the research method with fifty students of SMA Negeri 2 Binjai as the sample. The improvement was observed in 2 cycles. The finding results showed that from 19 to 38 students, more students received scores over the Minimum Completeness Criteria. Additionally, it went from 38% to 76% in percentage form. Students believe that the Orai app makes learning English less stressful and more enjoyable. After using the Orai application, it can be stated that the students' speaking skills have improved better.